Soil microbiome manipulation and its effect on the soil-plant interface - Arruda, Bruna (2020)
The aim of this project was to evaluate the effect of soil microbiome manipulation on microorganism relationship with soil and plant. Among these relationships are mycorrhizae. Many factors are determinant for its occurrence, including the soil microbial community. Our results showed that the effect of soil microbial community on mycorrhization depends on the plant species. Mycorrization in brachiaria was impaired by microbiome manipulation, but certain species of arbuscular mycorrhizal fungi were able to colonize crotalaria even under soil with reduced microbial community. To determine mycorrhizal colonization rates, microscopy is currently used, but it is a subjective analysis. To eliminate this issue, molecular techniques such as real-time PCR (qPCR) may be an alternative to standardize this assessment. Our results showed that the set of primers FLR3 and FLR4 showed a correlation of 0.73 between the microscopic and qPCR analyzes, thus being a promising alternative for mycorrhiza analyzes. In addition to soil microorganisms that assist plants in the absorption of P, the application of phosphate fertilizers is a practice used to supply this nutrient. However, we observed that the application of P did not compensate for the effect of high competition between plant and soil microorganisms by P. Brachiaria presented higher P uptake and dry matter accumulation when cultivated under soil with reduced microbial diversity. On the other hand, crotalaria showed a neutral effect for microbial manipulation. Studies involving soil microbial manipulation may use techniques such as soil autoclaving. This technique uses high temperature and pressure that together eliminate most of the microorganisms, which can also affect soil chemistry. Our results showed that in autoclaved soil 14CO2 emission via microbial respiration was null and there was no change in total N compared to natural soil, but there was an increase in N-NH4 compared to N-NO3. In addition, the autoclaving procedure did not alter soil 31P concentration, but reduced labile 33P activity. Studies on responses of different species of plants grown in soils with different levels of soil microbial diversity are needed to understand nutrient cycling such as N and P. Our results showed that brachiaria increased dry matter, N and P uptake when cultivated under soil that suffered microbiome reduction during the 1st cycle of the plant. For the 2nd cycle, brachiaria increased N uptake but no increments in shoot dry mass when grown in manipulated soil compared to soil without microbial manipulation. On the other hand, crotalaria was not affected by microbiome manipulation for shoot dry matter, N and P absorption. Thus, the results of this thesis may help in the management of biologically degraded areas to ensure greater sustainability in these systems.